Design and analysis of wind tunnel for scale model analysis - Mohamad Zulhairi Luqman Radzuan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Design and analysis of wind tunnel for scale model analysis was the research for built a device that use in aerodymics research to study the effect of air flow past to an object produced by a fan that was powered by a motor. The wind tunnel was designed to observe, demonstrate and investigate the characteristic of air by using smoke flow as the indicator to illustrate the airflow past an object.